Non Invasive Detection of Dengue Viruses from Saliva: In vitro Study - Saksono, Budi (ANNALES BOGORIENSES, 2018)
In the previous paper, we had succeeded in developing an early detection system of dengue viruses using Sugar liganded Gold Nano Particle (SGNP) only from 6 μL serum. It has been reported that dengue virus is also detected in the saliva and urine of the patient. The evidences lead to the possibility of developing non-invasive methods of dengue virus detection. In this in vitro study, we evaluated the utility of SGNP to capture and concentrate dengue virion in 10% saliva solution. The results showed that dengue virion was successfully detected in 10% of saliva solution. Analysis of virion stability during storage showed that virions in salivary samples were stable up to 3 days at temperature wherease the RNA has significantly degraded. Although still a preliminary study, the data obtained show the prospect of SGNP as a non-invasive dengue virus detection method, as well as the development of POC (Point of Care) method. Clinical trials using saliva from dengue viruses infected patients need to be done to prove the effectiveness of the SGNP method.